Prinsip Hukum Kedudukan Perempuan Dalam Hukum Waris Adat Masyarakat Banjar - Muzainah, Gusti (Muadalah, 2014)
The legal principles of women position in the Banjar community customary law are reflected from the legal norms used in the division of inheritance in lembaga damaiÂ  (peace institute) by means of peaceful settlement (islah /faraid islah). The process in the so called lembaga damai shows how women position is recognized as heir. This study is conducted to identify the legal norms of inheritance and the legal norms of women position in the Banjar community customary law.This study employs normative methods which data is drawn from primary, secondary and tertiary legal materials and from in depth interviews with the key informant. The result of the study shows that the Banjar legal norms on inheritance which is implemented in the lembaga damai is executed with peace settlement (islah/faraidh islah). Women are recognized as heir and their part of inheritance is relativeâcan be larger than men, can be equal to men, or can be less than men. This relative magnitude of inheritance indicates that the principle of divine, the principal of benefit and balance which it all rest on âmaslahah mursalahâ proposition are well applied.